Teaching Motivation, Mentorship, and Teaching Performance among Pre-Service Teachers - Aldrin John Tugap; John Donde Ampatin; Franz King Sibag; AV Francis H Secretaria; Hannah Mae C Pamilgan; Abdul J Jamra (Goodwood Publishing, 2026)
Purpose: This study quantitatively assessed the influence of teaching motivation and mentorship on the teaching performance of Pre-Service Teachers (PSTs) at Davao del Norte State College during the 2024–2025 academic year. Research Methodology: A quantitative correlational design was utilized. Data were collected from 196 pre-service teachers selected via stratified random sampling using the Factors Influencing Teaching-Choice Scale (FIT), Mentoring Relationship Challenges Scale (MRCS), and official performance rating sheets. Statistical analysis included mean, standard deviation, and Pearson's r. Results: Pre-service teachers demonstrated a very high level of motivation (M=4.27) and a high level of mentorship (M=3.97). The teaching performance was exemplary, with an average rating of 92.97. However, no significant relationship was found between motivation (p=0.558) or mentorship (p=0.383) and actual teaching performance. Conclusions: Although PSTs are highly motivated and driven primarily by altruism and receive strong mentorship, these factors did not statistically correlate with instructional quality in this specific group. Limitations: This study utilized a quantitative design that focused on numerical outcomes and may not have fully captured the qualitative nuances of the mentor-mentee relationship. Contributions: These findings suggest that teacher education programmes should explore other variables, such as classroom management or institutional support, that may more directly impact instructional quality.